2018
DOI: 10.1155/2018/7459496
|View full text |Cite
|
Sign up to set email alerts
|

Decorin, Tenascin C, Total Antioxidant, and Total Oxidant Level Changes in Patients with Pseudoexfoliation Syndrome

Abstract: Purpose Pseudoexfoliation syndrome (PEX) is an eye disease that develops under the influence of regional population differences, genetic factors, age, and environmental factors and is characterized by visualization of a gray-white fibrogranular substance in the lens anterior capsule and/or pupil margin during anterior segment examination. The underlying biochemical mechanisms of the disease have not yet been fully elucidated. Therefore, this study was designed to show the changes in aqueous humor and blood ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…[6,25,26] On the other hand, different environmental factors such as solar radiation, oxidant/antioxidant imbalance, and dietary factors such as high coffee consumption and low dietary folate intake are associated with increased risk of PXF. [7][8][9][10]27] The role of trace elements in the hormonal imbalance has been investigated in previous studies. Zhang et al showed that Cu level increases and Zn level decreases in polycystic ovarian syndrome which is related to hormonal imbalance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6,25,26] On the other hand, different environmental factors such as solar radiation, oxidant/antioxidant imbalance, and dietary factors such as high coffee consumption and low dietary folate intake are associated with increased risk of PXF. [7][8][9][10]27] The role of trace elements in the hormonal imbalance has been investigated in previous studies. Zhang et al showed that Cu level increases and Zn level decreases in polycystic ovarian syndrome which is related to hormonal imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The etiology of PXF syndrome is not exactly known, but a multifactorial complex model including genetic inheritance combined with environmental factors, such as geographic location, UV exposure, and decreased serum and aqueous levels of antioxidants have been suggested as the contributing factors. [5][6][7][8][9][10] According to the recent studies, oxidative stress plays a key role in the pathogenesis of PXF syndrome and decreased levels of different antioxidants has been investigated in the serum and aqueous samples of patients suffering from PXF syndrome. [2][3][4][8][9][10] Although in a few studies, the serum and aqueous levels of some microelements have been determined in these patients, the possible effect of microelements on the prevalence and/or severity of PXF syndrome has remained controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Icel et al [40] reported that TOS level was found to be significantly higher while TAS was found to be low in the study of diabetic rats. Oruç et al [41] found that the TOS value was high while the TAS value was found low in humorous aqueous of pseudoexfoliation patients, and they reported that normal these levels may slow the progression of pseudoexfoliation syndrome. In a study conducted by Altını ık et al [42] in patients with retinal vein occlusion, it was found that the oxidative stress index in humor aqueous was high, while TAS values were low.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that it binds to collagen fibrils. However, its role in the PEXS pathogenesis is not specified yet 47 . When it comes to GAGs, studies have shown that patients with PEXS tend to have higher levels of hyaluronan (HA) compared to healthy individuals.…”
Section: The Role Of Ecm In Pexsmentioning
confidence: 99%